Cannabis use among Navy personnel in Sri Lanka: a cross sectional study. (December 2016) - Silva, Varuni; Jayasekera, Nicholas; Hanwella, Raveen
Abstract Background Prevalence of cannabis use among military populations vary. There is evidence that drug use is associated with combat exposure and PTSD. The objective of the study was to assess the prevalence of cannabis use among Sri Lanka Navy (SLN) personnel and to identify any relationship with cannabis use and combat exposure. Methods This cross sectional study was carried out among representative samples of SLN Special Forces (Special Boat Squadron) and regular forces deployed in combat areas. Both Special Forces and regular forces were selected using simple random sampling. Personnel who had served continuously in combat areas during the 1 year period prior to end of combat operations were included in the study. Cannabis use was defined as smoking cannabis at least once during the past 12 months. Results The sample consisted of 259 Special Forces and 412 regular navy personnel. Prevalence of cannabis use was 5.22 % (95 % CI 3.53–6.9). There was no significant difference in prevalence of cannabis use among Special Forces personnel compared to regular forces. Cannabis use was significantly higher in the age group 18–24 years [OR 4.42 (95 % CI 2.18–8.97)], personnel who were never married [OR 2.02 (95 % CI 0.99–4.12)], or had an educational level less than GCE O'Level [OR 4.02 (95 % CI 1.17–13.78)]. There was significant association between cannabis use and hazardous alcohol use [adjusted OR 5.47 (95 % CI 2.65–11.28)], PTSD [adjusted OR 4.20 (95 % CI 1.08–16.38)], GHQ caseness [adjusted OR 2.83 (95 % CI 1.18–6.79)] and multiple somatic complaints [adjusted OR 3.61 (95 % CI 1.5–8.7)]. Cannabis use was not associated with smoking. Risk of cannabis use was less in those who had seen dead or wounded [adjusted OR 0.42 (95 % CI 0.20–0.85)]. Experiencing hostility from civilians was the only combat exposure that significantly increased the risk of cannabis use [adjusted OR 4.06 (95 % CI 1.06–15.56)]. Conclusions Among Sri Lanka Navy personnel exposed to combat cannabis use was significantly associated with hazardous alcohol use but not smoking. PTSD and other adverse mental health outcomes were associated with an increased risk of cannabis use. Exposure to combat was not associated with increased risk of cannabis use.